"Age is just a number" the normalization of grooming behavior through online statements across socioeconomic statuses - Alde, Howard A.; Baldos, John Ross B.; Novales, Angelina Wayne P. (2023)
The present study aims to determine the relationship between socioeconomic status and the frequency of exposure and agreeableness to grooming statements found on Facebook. Respondents were freshmen students who were conveniently selected from two colleges in a university in Tacloban City. A survey was conducted to the respondents and a follow-up semi-structured interview was conducted to three participants from the same pool of respondents. The analysis revealed that there is no significant relationship between socioeconomic status and the frequency of exposure and agreeableness to grooming statements. However, there is a moderate correlation between the frequency of exposure and agreeableness to grooming statements. Given the data, it was found that gender might be an important variable for future studies as men show a strong correlation between the frequency of exposure and agreeableness to grooming statements compared to their women counterparts who had a moderate correlation.